ASUHAN KEBIDANAN PADA BAYI IBU Z DENGAN PENERAPAN TEKNIK OVER YOUR SHOULDER UNTUK MENGATASI GUMOH TAHUN 2025 - Rahmi, Liza; Asmanidar, Asmanidar; Norisa, Nanda; Zahara, Evi (SINERGI : Jurnal Riset Ilmiah, 2025)
Introduction: Spitting up (Regurgitation) is a common problem in infants, especially infants aged 0-3 months, and in Indonesia 25% of infants experience spitting up more than 4 times a day in the first month. Spitting up often occurs in infants after breastfeeding, and as the baby gets older, it is estimated that the incidence of spitting up will decrease, namely 8-10% in infants aged 9-12 months and 5% in infants aged 18 months, efforts that can be made to overcome spitting up or regurgitation in infants are using the Over Your Shoulder technique. Objective: This study aims to provide comprehensive midwifery care, especially for infants of mother Z who experience spitting up or regurgitation after breastfeeding using the Over Your Shoulder technique. Research Method: This study is a case study with a qualitative descriptive approach. This study was conducted by exploring and providing comprehensive midwifery care to infants of mother Z starting from 3 days after delivery with complications of spitting up using the Over Your Shoulder technique. Research results: Comprehensive midwifery care for mother Z's baby has been carried out starting from 3 days after delivery based on the results of the anamesa, it was found that the baby often experienced spit up some time after the baby was breastfed. So that the Over Your Shoulder technique was applied for 5-10 minutes, after which the baby burped, and visits were made 2 times. The care provided was to apply the Over Your Shoulder technique to mother Z's baby after spit up could be resolved properly. Conclusion: Midwifery care for mother Z's baby was carried out using the Over Your Shoulder technique, namely placing the baby on the mother's shoulder or chest and then patting the baby's back until he burps. The results of midwifery care carried out using this technique showed that there was no regurgitation in mother Z's baby during monitoring, so it can be concluded that the Over Your Shoulder technique has proven effective and there is no gap between theory and practice.